2020
DOI: 10.24018/ejbmr.2020.5.6.606
|View full text |Cite
|
Sign up to set email alerts
|

Audit Evidence and Financial Statement Quality in Government Owned Companies in Rivers State, Nigeria

Abstract: The spate of Accounting scandals and Financial crisis in firms have undermined investors trust concerning financial statements, and as such has raised concerns and criticisms about the quality of financial statements. In order to regain investors’ confidence on financial statements, the audit function lends credibility to the financial statements, particularly through obtaining audit evidence. Therefore, this study empirically investigated the extent of relationship between audit evidence and financial stateme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…To begin with, it was observed that most relevant studies by Nigerian researchers on marketing ethics centered on business ethics in the service sector (Ebitu & Beredugo, 2015); manufacturing sector (Ango, 2018); and SMEs (Agwor & Osho, 2017). This entails that the main focus of this researchethical marketing practiceshas therefore not attracted sufficient scrutiny from Nigerian researchers especially in the context of petrol stations.…”
Section: Problem Statementmentioning
confidence: 99%
“…To begin with, it was observed that most relevant studies by Nigerian researchers on marketing ethics centered on business ethics in the service sector (Ebitu & Beredugo, 2015); manufacturing sector (Ango, 2018); and SMEs (Agwor & Osho, 2017). This entails that the main focus of this researchethical marketing practiceshas therefore not attracted sufficient scrutiny from Nigerian researchers especially in the context of petrol stations.…”
Section: Problem Statementmentioning
confidence: 99%
“…Through periodic elections and control structure, elected and appointed officials are held accountable for their actions while holding public office. (4) Social Accountability: This is a demand driven approach that relies on civic engagement and involves ordinary citizens and groups exacting greater accountability for public actions and outcomes (Agwor & Akani, 2017). The concept of financial accountability of local governments in Nigeria, is all about holding and ensuring that stewards with resources which are not theirs give an accurate and up to date accounts of what they have done with the resources, with the resources, with a view to ascertaining whether or not they have individually or collectively conformed with, violated, manipulated, achieved or even thwarted the objectives of the owners of the resources (Omolaye 2015).…”
Section: Conceptual Reviewmentioning
confidence: 99%
“…Once the quality of financial reporting is enhanced, the SACCO members build confidence among the managers, thus entrusting them with more financial resources (Owolaba and Dada, 2011). More so, Accountability is considered as a means of providing relevant information for wise economic decisions (Agwor and Akani, 2017). Also, in order to attract members to actively participate in the cooperatives' business activities, there is a need for higher financial returns by SACCOs, as a portion of which will be allocated to the members in form of dividend pay-out (Shafawaty, Ram, and Azizi, 2016).…”
Section: Introductionmentioning
confidence: 99%